Synthesis and Pharmacological Activities of Some Schiff Bases Derived from N,N’-Bis(4-ethoxyphenyl)malonamide - Pradhan, Alka; Daw, Devidas; Deshmukh, Deepak; Tripathi, Anil (Asian Journal of Chemistry, 2010)
Series of the Schiff Bases (1a-m) of N,N'-bis(4-ethoxyphenyl) malonamide (1) are synthesized by the condensation reaction between compound 1 and substituted aromatic amines. Compound 1 is obtained by condensation of 4-ethoxy aniline and diethylmalonate. The resulting compounds are characterized by spectral data and evaluated for antihistaminic activity. Most of the compounds have shown interesting biological activity.